Optimal investment for retail investors - Christoph Belak; Lukas Mich; Frank T. Seifried (Mathematical Finance, 2021)
We study optimal portfolio decisions for a retail investor that faces a strictly positive transaction cost in a classical Black-Scholes market. We provide a construction of optimal trading strategies and characterize the value function as the unique viscosity solution of the associated quasi-variational inequalities. Moreover, we numerically investigate the optimal trading regions for a variety of real-world cost structures faced by retail investors. We find that the cost structure has a strong effect on the qualitative shape of the no-trading region and optimal~strategies.
Keywords: 519; portfolio optimization; transaction costs; retail investor